PARTISIPASI MASYARAKAT DALAM PENYUSUNAN RENCANA PEMBANGUNAN DESA DI DESA TAMBAROBONE KECAMATAN BUNGKU UTARA KABUPATEN MOROWALI UTARA - Wijaksono, Ali; Tawil, Muzakir; Rapi, Muhammad (JPS: Journal of Publicness Studies, 2025)
This research aims to understand how community participation in the preparation of the Village Development Plan in Tambarobone Village, Bungku Utara District, North Morowali Regency. The research method used is descriptive qualitative. The data collection techniques employed are observation, interviews, and documentation. The research location coincides with Tambarobone Village, Bungku Utara District, North Morowali Regency. The theory used in this research is the theory of Bintoro Tjokroamidjojo (2005:226), which consists of three aspects that influence community participation: Leadership Factor, Communication Factor, and Education Factor. The research results show that from the aspect of leadership, the Tambarobone village government is doing well because it has made efforts to implement the concept of participatory planning. Similarly, from the aspect of communication, the Tambarobone village government has established good communication with the village community. Meanwhile, from the aspect of education, it is still quite good. This is because the relatively low level of education among the people in Tambarobone village affects community participation in development planning.